With or Without You: Altered Plant Response to Boron-Deficiency in Hydroponically Grown Grapevines Infected by Grapevine Pinot Gris Virus Suggests a Relation Between Grapevine Leaf Mottling and Deformation Symptom Occurrence and Boron Plant Availability - Buoso, Sara; Pagliari, Laura; Musetti, Rita; Fornasier, Flavio; Martini, Marta; Loschi, Alberto; Fontanella, Maria Chiara; Ermacora, Paolo (Frontiers in Plant Science, 2020)
Despite the increasing spread of Grapevine Leaf Mottling and Deformation (GLMD) worldwide, little is known about its aetiology. After identification of grapevine Pinot gris virus (GPGV) as the presumptive causal agent of the disease in 2015, various publications have evaluated GPGV involvement in GLMD. Nevertheless, there are only partial clues to explain the presence of GPGV in both symptomatic and asymptomatic grapevines and the mechanisms that trigger symptom development, and so a consideration of new factors is required. Given the similarities between GLMD and boron (B)-deficiency symptoms in grapevine plants, we posited that GPGV interferes in B homeostasis. By using a hydroponic system to control B availability, we investigated the effects of different B supplies on grapevine phenotype and those of GPGV infection on B acquisition and translocation machinery, by means of microscopy, ionomic and gene expression analyses in both roots and leaves. The transcription of the genes regulating B homeostasis was unaffected by the presence of GPGV alone, but was severely altered in plants exposed to both GPGV infection and B-deficiency, allowing us to speculate that the capricious and patchy occurrence of GLMD symptoms in the field may not be related solely to GPGV, but to GPGV interference in plant responses to different B availabilities. This hypothesis found preliminary positive confirmations in analyses on field-grown plants.